Influence Of Social Norms And Spiritual Tendencies To Moral Considerations In Religious School Students - Mohd Zailani Mohd Yusoff; Mohamad Khairi Othman (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2017)
The main purpose of this study is to trace information related to the influence of social norms and spiritual tendencies to moral considerations in religious school students.This study aims to identify the influence of the dimensions of Islamic spiritualtendencies and the dimension of social customs to moral considerations based onestablished schemes. Three measuring tools were used in this study, namely UjianSkema taakulan Akhlak (UPSTA), Kuesioner Kecenderungan Kerohanian Islam(ISDQ) dan Tes Sikap dan Pegangan Terhadap Standar Prevalensi Sosial (USPSK).The subjects of the study consisted of 500 students who were divided into genderaccording to the type of religious high school in the state of Kelantan which wererandomly selected from Sekolah Menengah Kebangsaan Agama (SMKA), MaahadMuhammadi (MM), Maahad Tahfiz Al-Quran / Sains (MTAQ / MTS), SekolahAgama Rakyat (SAR) dan Sekolah Agama Swasta (SAS). This review review uses aquantitative method based on cross-sectional research approach (Cross Sectional).Data were collected from the above three tests and analyzed by using statisticalanalysis of stepwise multiple regression at significant degree p <0.05. The results ofthe study show that dimensions of faith and faith play a powerful role in the moralconsideration of high school religious students. The findings also show the dimensionsof faith, intrinsic dimensions and extrinsic dimensions in the aspect of Islamicspiritual tendency to have significant influence (R² = .465, sig.) On the moralconsiderations of religious school students. However, the dimensions of human rightswithin social norms varied only (R² = .017, sig .003) on moral considerations amongreligious school students in Kelantan. This review provides a fresh understanding ofthe moral issues of religious secondary school students. The tendency of religiousschool students on Islamic spiritual aspects plays an important role in determiningthe quality of their moral considerations.